The Effect of Growth Opportunity And Good Corporate Governance of Accounting Prudence in State-Owned Companies - Alsi Agusdinar Alsi Agusdinar Rizki; Susi Retna Cahyaningyas; Indria Puspitasari Lenap (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This study aims to determine the effect of Growth Opportunity, Independent Commissioners and Audit Committee on Accounting Prudence in State-Owned Enterprises (BUMN) companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The data used in this research is secondary data. The sample consists of 27 state-owned companies. The sampling technique in this study used purposive sampling. The analytical tool used to test the hypothesis in this study is multiple linear regression analysis with the help of the SSPS version 26 program. The results of the model feasibility test show that the Growth Opportunity, Independent Commissioner and Audit Committee variables together have no effect on Accounting Prudence. The results of this study contain implications that the results of this study can be a consideration for companies in applying the principles of Prudence Accounting in order to prevent information asymmetry between agents and principals and avoid opportunistic behavior of managers. The results of this study can also be taken into consideration in determining agency costs.